THE EFFECT OF HYDROGEL AND WATER ON THE GROWTH OF SHALLOT PLANTS (Allium ascolanicum L) - Ginting, Sulaiman; Nasution, Usman; Purwaningrum, Yayuk; Pradip Dalimunthe , Muhammad (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
AbstractThe research was carried out in the greenhouse of the Faculty of Agriculture, Islamic University of North Sumatra. Gedung Johor Village, Medan Johor District, Medan City, North Sumatra Province with an altitude of ± 25 m above sea level. This research will be conducted from December 2018 to February 2019. The aim of this study was to determine the effect of hydrogel and water on the growth of shallots (Allium ascolanicum L ). The design used was a factorial Completely Randomized Design (CRD) which consisted of two factors, namely: the hydrogel administration factor consisted of 4 levels, namely: Control, 1 g/pot, 2 g/pot, 3 g/pot and the volume of water sprinkling consisted of 3 levels, namely: 125 ml/pot (0.25 soil water content field capacity), 250 ml/pot (0.5 soil water content field capacity), 500 ml/pot (soil water content field capacity). The results showed that water spray affected growth, namely on plant height and plant wet weight. The hydrogel did not affect growth, but the combination of water spray and hydrogel affected the growth of plant height, plant wet weight and efficiency of watering as much as 250 ml where plant height and plant wet weight of the 250 ml watering treatment and the 3 g hydrogel were not significantly different from the 500 ml watering treatment and 3 g hydrogel.